Effect of estradiol on proliferation and differentiation of side population stem/progenitor cells from murine endometrium - Xu Jing; Hu Fei-Fei; Cui Yu-Gui; Luo Jian; Jiang Chun-Yan; Gao Li; Qian Xiao-Qiao; Mao Yun-Dong; Liu Jia-Yin (BMC, 2011)
Abstract Background In our previous study, endometrium side population cells (SP cells) were isolated from postpartum murine uterus, and characterized by a heterogeneous population of stem/progenitor cells. In this study, we investigated the effect of estrogen on the proliferation and differentiation of SP cells. Methods SP and non-SP cells of postpartum murine endometrium were isolated by DNA dye Hoechst 33342. The expression of estrogen receptor 1 (ESR1) was measured by reverse transcription polymerase chain reaction (RT-PCR), Real-time PCR, Western blot, immunofluorescence and immunohistochemistry. The proliferation and differentiation of SP cells treated with different concentrations [10(-8) M-10(-6) M] of estradiol (E2) and E2+ ICI182780 (Faslodex, inhibitor of ESR1) were measured by 3-(4, 5-dimethylthiazoly1-2)-2,5-diphenyltetrazolium bromide(MTT) and clonogenic assays. Results (1) SP cells expressed ESR1 at a higher level than non-SP cells. (2) The level of E2 in the serum and the expression of ESR1 in the uterus of postpartum murine changed in the same manner with the ratio of SP cells to total uterus cells at a different postpartum time point. ESR1, as ABCG2 is also predominantly located in the stroma and the glandular epithelium of the uterus. (3) 10(-6) M E2 notably promoted the proliferation of SP cells after treatment for 24 h. This effect could be inhibited by ICI182780. E2 at the concentration of 10(-7) M or 10(-8) M was sent to impair the large cloning efficiency (CE) of SP cells. Conclusions The effect of estrogen on the proliferation and differentiation of endometrium SP cells via ESR1 was observed and it was in a concentration dependent fashion. Clearly, more work is needed to understand the in vivo effect of E2 at the physiological concentration on the differentiation of SP cells.